Resource decline and adaptation through time: fishers in San Miguel Bay, Philippines 1980-1993 - Sunderlin, William D. (1995)
This article examines social conditions in a bay experiencing population growth, gear conflict, overfishing, and general resource declince. Sample surveys of fishing households caried out in 1980 and 1993 in nine villages of San Miguel Bay reveal patterns of continuity and change. The key continuity is sustained overall population growth in fishing villages. Among the key forms of change are those which demonstrate a degree of adaptation to resource decline: decreased participation in fishing; greater reliance of fishing households on nonfishing income; increased dependence on remittances of nonhouseholds labor; and dramatic growth in the number of fishing organizations involved in resource management. The findings suggest that resource management policies should be patterned after spontaneous adaptations to resource decline.